Investigations into Two New Variants of the Hybrid Incremental Sheet Forming Processes - Zhao, Xuelei (2023)
The incremental sheet forming (ISF) process has drawn significant attention over the last two decades. Due to its excellent adaptability and flexibility, the ISF process can be widely used in rapid prototyping, small batch production, and manufacture of customised products. The basic concept of the ISF process is to use a forming tool moving along a predefined tool path and to deform the blank sheet into a designed product through gradual deformations of sheet materials. The motion of the forming tool is controlled by a computer numerical controlled (CNC) milling machine. Easy control of the tool motion and no need of forming dies or complex tooling makes the ISF process flexible and cost-effective. Despite extensive research on the ISF process, a number of limitations and challenges still restrict the conventional ISF processes from being widely used. Researchers have looked into the development of hybrid ISF processes that combine the ISF with other forming processes in the past decade. In this research, two new variants of the hybrid ISF processes have been proposed: the hybrid stretch forming and double-layer two-point incremental sheet forming (hybrid stretch forming and DL-TPIF) process and the flexible multi-layer multi-point incremental sheet forming (flexible ML-MPIF) process. The proposed hybrid processes are intended to overcome the limitations of the conventional ISF processes, including poor surface roughness, excessive sheet thinning, and low geometrical accuracy. This thesis demonstrated the benefits of the proposed new variants of hybrid processes in comparison with the conventional ISF processes through extensive experimentation and finite element (FE) analysis. The hybrid stretch forming and DL-TPIF process enable seamless integration of the two separate processes, which can offer the possibility of maintaining the advantages of both forming processes. The difference between the conventional two-point incremental sheet forming (TPIF) process with a dummy sheet and the proposed DL-TPIF process was that the target blank sheet was not rigidly clamped by the blank holders. Thus, more material from the clamping region would be drawn into the deformation region. The new hybrid stretch forming and DL-TPIF process has been evaluated by two case studies through forming a dome and irregular shapes by experimental testing and FE simulations. Three pre-stretching conditions (i.e., 0 mm, 15 mm, and full depth) were examined to determine the effect of prior stretching operation. The results showed the maximum thickness reduction of the dome shape produced by the new stretch forming and DL-TPIF process was only 13.8%, which was less than 1/3 of that obtained from the conventional TPIF process (45%). In addition, the geometrical accuracy and surface quality were also improved by using this new variant of the hybrid forming process. The increase in pre-stretching depth significantly reduced sheet thinning and geometrical inaccuracy. In the flexible ML-MPIF process, a new flexible multi-point die was generated to replace the conventional multi-point fixed die. The target blank sheet was placed between the upper dummy sheet and a polyurethane sheet. The proposed flexible multi-point die enabled all the multi-point pins to be in contact with and support the blank sheet from the start to the end of the forming process. Moreover, it was different from the conventional multi-point incremental sheet forming (MPIF) process in that the target blank sheet can be deformed without clamping constraint. Full comparative investigations into the conventional and flexible MPIF processes, and ML-MPIF processes with flexible multi-point and fixed multi-point dies were conducted through experimental testing and FE simulations. The results showed that the maximum thickness reduction in the flexible ML-MPIF process had been significantly reduced from 35% to 5% as compared to the conventional MPIF process, and the thickness distribution has become more uniform. The proposed new variants of hybrid forming processes were shown to have the benefits of significantly reduced sheet thinning and achieve improvements in thickness distribution, geometrical accuracy, and surface quality as compared to the conventional ISF processes. However, in the flexible ML-MPIF process, the use of a polymer sheet could lead to large dimensional deviations. Further research can focus on the new buffer pads to improve geometrical accuracy and reduce the springback when employing the multi-point die. Despite the investigations on the proposed new variants of hybrid forming processes, it is still challenging to evaluate the behaviour of these hybrid forming processes in producing some complex parts for industrial applications. There is considerable scope to explore the viability of the hybrid forming processes in producing some hard-to-deform material at room temperature or under heated conditions to improve the formability.